Promising Antimicrobial and Antioxidant Extracts of Murta Leaves (Ugni Molinae Turcz): Shelf-Life Extension and Food Safety - Guarda-Moraga, A; Rodriguez-Mercado, F; Galotto-Lopez, M (Elsevier Ltd, 2014)
Murta leaves are known for their beneficial effects since long time. Therefore, the aim of present study was to determine the antimicrobial and antioxidant activity of different extracts from Murta (Ugni molinae Turcz) leaves. Three extracts were obtained from Murta leaves using water or ethanol (50%, v/v) as solvents with different solid-to-solvent-ratios. The extracts were characterized in terms of their antimicrobial activity, antioxidant capacity and total polyphenol content. An extract from 1.5. g of Murta leaves obtained with 20. mL of 50% ethanol showed the highest polyphenol content with 309.4. mg. gallic acid/g and the highest growth reduction of Listeria innocua (ATCC 33090), inhibiting 4.9 and 4.8 log cycles after 2 and 24. h of contact, respectively. The ethanolic extract of Murta leaves provides a natural potential antioxidant and antibacterial additive for food production. © 2014 Elsevier Ltd.